If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -5)(-5) = 0 Reorder the terms: (-5 + x)(-5) = 0 Reorder the terms for easier multiplication: -5(-5 + x) = 0 (-5 * -5 + x * -5) = 0 (25 + -5x) = 0 Solving 25 + -5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -5x = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -5x = 0 + -25 -5x = 0 + -25 Combine like terms: 0 + -25 = -25 -5x = -25 Divide each side by '-5'. x = 5 Simplifying x = 5
| 3x-3+45=-3x | | -6x+6(7x-15)=198 | | 6(5x+1)=5x-8X | | 3(4x+3)=2-5(7-x) | | 164x-82=738 | | 7(3x+1)=3x-8x | | 0.02x+0.5=0.35x+1.2 | | 5x+1=-13x+15 | | 2z+96=15z-85z | | 21x^2=7x | | x^2+2i=0 | | an=5n-8 | | -9+90=9x-90 | | 5x-95=x | | -8y-2=-7y-7 | | 3-4x+6-7=42 | | lnx=0.85 | | x^2+12x=540 | | 4(x-3)+2x=10 | | 1+15=-4(4x-4) | | 7x+9y=3+9x | | 30x^2+273x-270=0 | | m+11/8=8 | | 1+15=4(4x-4) | | 15x-5=25x+3 | | 2(x-3)+10=18 | | -4(x+1)-14=16+2 | | x+7+4x-3=3x+x-2x+16 | | 5k-3/(-3) | | y=-(1/3)x | | y=7000x+b | | 5k-3/3 |